Voicing in English - Zaynab Faysal Hussein; Abbas Fadhil Lutfi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Voicing in phonetics has long been of interest to linguists and others passionate about languages. Besides, understanding the nuances of voicing is essential in phonetic analysis and language learning. This paper enhances the understanding of voicing in English speech sounds. It strives to examine the presence and absence of voicing in various contexts, both in consonant and vowel sounds. The questions tackled here include: How does the English language manifest voicing in its sound system? How does voicing affect the articulation and perception of consonant and vowel sounds? In what ways do voicing and devoicing enhance the distinctiveness of speech sounds? This paper hypothesizes that the English language has its norms that govern the presence and absence of voicing phenomenon; hence, a complete understanding of consonant and vowel sounds is inevitable for adequately analyzing and comprehending the intricacies of voicing in English. This study adopts a descriptive qualitative method of analysis. Most of the data are taken from books on phonetics and phonology, as well as academic articles and researches. The paper concludes that voicing in English displays different patterns in distinctive phonetic categories, comprising plosives, fricatives, affricates, nasals, approximants, and vowels. The findings of this paper designate that the occurrence of voicing and its absence (devoicing) is considerably affected by the contextual nuances of speech sounds.